Preparation method of graphene / polyimide / graphene three-dimensional structure permeable membrane
The graphene layer is generated on the polyiline thin film through laser induction technology to form a graphene/polytamine/graphene three -dimensional structure osmotic membrane, which solves the problem of insufficient performance of polytamide diaphragm in the existing technology. The radioactive wastewater treatment effect of high -throughput and high intercepting rate is achieved.
Patent Information
- Application Number
- CN202411602399.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to meet the high throughput and high interception rate requirements of polyimide semipermeable membranes when treating radioactive wastewater, and there are challenges in traditional graphene preparation and transfer technologies.
Use laser induction technology to generate graphene layers on both sides of the polyanamide film, forming a graphene/polytamine/graphene three -dimensional structure osmotic membrane, and further optimized the membrane through the process of rotation and solidification of the modifier solution and solidification process. Performance.
It achieves an efficient combination of graphene and polyimide, improves the permeation flux and rejection rate of the membrane, has good chemical stability and mechanical strength, and is suitable for radioactive wastewater treatment in complex environments.
Smart Images

Figure CN119345911A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of radioactive wastewater treatment, and specifically relates to a method for preparing a graphene / polyimide / graphene three-dimensional structure permeation membrane. Background Art
[0002] With the rapid economic development and the increase in energy demand, new power generation methods are gradually replacing traditional power generation methods. Among the new power generation methods, nuclear energy is considered to be a clean energy source. Its zero emission, high energy density and reliability are the key reasons why nuclear power is so widely used in the world today. However, it will produce a large amount of radioactive hazardous waste, waste liquid and waste gas during normal operation. The treatment of radioactive waste liquid is an urgent need for treatment.
[0003] At present, the main methods used by most nuclear power plants in China to treat radioactive wastewater are: evaporation concentration, ion exchange, chemical precipitation and membrane treatment. The evaporation concentration method can concentrate most of the radioactive nuclides in the evaporation residue, but it consumes a lot of energy and has high operating and maintenance costs; the ion exchange method has good decontamination effect, is easy to operate and easy to automate, but it has high costs, strict use conditions and will produce waste resin that is difficult to handle after use; the chemical precipitation method is simple, low-cost, and removes more elements than the Guangdong Nuclear Technology Equipment is mature, but the waste liquid and precipitate after chemical precipitation treatment need to be treated secondary. Compared with the above-mentioned traditional treatment processes, membrane treatment technology has the advantages of high purification coefficient, stable system operation, low energy consumption and simple equipment, and has broad application prospects in radioactive wastewater treatment technology.
[0004] The membrane material selected for treating radioactive nuclear wastewater needs to have high permeability and good physical and chemical stability. The performance of the currently used polyethersulfone membrane (PES), polyetherketone membrane (PEK), polyimide membrane (PI), polyether urea membrane (PEI) and polypropylene membrane (PP) is difficult to meet the current treatment needs, and the permeation flux and retention rate of membrane separation materials need to be improved. Polyimide (PI) has been widely used in membrane treatment technology. Due to its high permeability, chemical stability and mechanical strength, polyimide membrane is an ideal choice for reverse osmosis (RO) membrane and nanofiltration (NF) membrane. At present, it has been widely used in water treatment, seawater desalination, wastewater treatment and other fields. In order to further improve the separation performance of polyimide semipermeable membrane and optimize its chemical properties at the same time, modification and modification methods can be carried out on the surface of polyimide.
[0005] Graphene is a two-dimensional grid composed of carbon atoms arranged in the form of a honeycomb lattice. Graphene has a high specific surface area, stable physical and chemical properties, and excellent mechanical properties. With a higher specific surface area and adsorption performance than activated carbon, it is gradually gaining attention from researchers in the field of water treatment. At present, graphene is mainly prepared by mechanical exfoliation, ultrasonic-assisted liquid phase exfoliation, chemical meteorological deposition, and chemical reduction graphene oxidation. Traditional graphene preparation and transfer technology still faces challenges. The composite technology of graphene and polyimide (PI) combines the excellent properties of graphene and polyimide to form a new type of functional material. Since polyimide material has excellent mechanical properties as a substrate, graphene as a filler can further enhance the strength and toughness of the membrane and improve its damage resistance. The unique pore structure of graphene gives the composite membrane good permeability and selectivity, making it have excellent performance in separation and filtration applications. The composite membrane can achieve efficient separation and remove impurities in water during reverse osmosis and nanofiltration. Both polyimide and graphene have good chemical stability and can withstand many chemicals and environmental conditions, so the composite membrane can maintain excellent stability in a variety of complex environments.
[0006] Laser-induced graphene (LIG) technology can form a composite structure of graphene and polyimide graphene in one step without the need for additional composite steps. LIG technology is a method of using laser to irradiate an organic polymer substrate with infrared laser to form a three-dimensional porous graphene structure. This method has high efficiency and generates graphene as a multilayer structure. Its main mechanism of action occurs on the surface of the PI substrate. Laser direct writing technology has been proven to be a reliable, mask-free and template-free method. Through this technology, people can obtain any pattern of graphene composited with PI materials, which greatly facilitates the preparation of graphene. The generated graphene is embedded in the polymer matrix as a filler, thus giving the composite material the characteristics of graphene. At present, the most widely studied is laser treatment of polyimide (PI) materials. Through laser induction, a continuous and uniform graphene layer can be generated on the surface of polyimide. At the same time, the instantaneous generation of gas products will lead to high surface pressure, which helps to form a LIG layer with a porous structure. This method can be implemented in other carbon-containing organic matter, such as bread, wood, paper and leaves. Based on the characteristics of LIG technology such as fast, patternable and low cost, it has broad application prospects and value.
[0007] The paper "Laser-induced porous graphene films from commercial polymers" first proposed a method for laser-induced graphene. On a commercial polyimide film, a CO2 infrared laser was used to ablate to obtain a porous graphene film with a three-dimensional grid. Specifically, the CO2 infrared laser was used to cause a sharp increase in the local temperature of the PI surface through laser irradiation, destroying the CO, C=O and NO bonds in the PI, releasing small atoms / molecules to re-form others, and at the same time, the edge carbon atom groups were rearranged and combined to form a graphene structure. The publication number is [CN110167877B], and the name is "Method for manufacturing laser-induced graphene and its composition". The invention uses a laser-induced graphene method to manufacture high-performance polymer materials (such as Kevlar) from natural renewable precursors (such as cloth and paper). The resulting laser-induced graphene material is used in electronic devices, anti-fouling surfaces, and water treatment technology.
[0008] The structure of polyimide semipermeable membrane is the main factor affecting its separation performance. The current traditional manufacturing process is difficult to meet the needs of high flux and high interception rate. Therefore, developing new methods to prepare semipermeable membranes with excellent filtration performance is the most critical issue in the entire membrane wastewater treatment. Summary of the invention
[0009] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0010] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0011] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a graphene / polyimide / graphene three-dimensional structure permeable membrane.
[0012] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0013] Laser-induced treatment of both sides of the polyimide film to obtain a graphene-polyimide-graphene composite film;
[0014] The modifier is dissolved in a solvent, heated in a water bath, and stirred to obtain a uniformly dispersed modifier solution;
[0015] The modifier solution is spin-coated on the front and back sides of the graphene-polyimide-graphene composite membrane and solidified to obtain a graphene / polyimide / graphene three-dimensional structure permeable membrane.
[0016] As a preferred solution of the method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane described in the present invention, wherein: the laser power of the laser induction is 5 to 10 W, and the laser moving rate is 800 to 1000 mm / s.
[0017] As a preferred solution of the method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane described in the present invention, the modifier includes one of polyvinyl alcohol, polyacrylonitrile and chitosan.
[0018] As a preferred solution of the method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane of the present invention, the concentration of the modifier in the solvent is 1.5-10wt%.
[0019] As a preferred embodiment of the method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane of the present invention, the solvent comprises one of water, 1-methyl-2-pyrrolidone or an aqueous solution containing acetic acid.
[0020] As a preferred solution of the method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane of the present invention, the concentration of acetic acid in the aqueous solution containing acetic acid is 1-2%.
[0021] As a preferred embodiment of the method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane of the present invention, the water bath heating temperature is 90-95° C. and the heating time is 1-2 hours.
[0022] As a preferred solution of the method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane described in the present invention, the rotation speed of the spin coating is 2500-3000 rpm, and the time is 20-30s.
[0023] As a preferred solution of the method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane described in the present invention, wherein: the curing temperature is 70-75° C. and the curing time is 1-2 hours.
[0024] As a preferred embodiment of the method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane of the present invention, the amount of the modifier solution is 15-20 μL / cm 2 .
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention provides a method for preparing a graphene / polyimide / graphene three-dimensional structure permeable membrane. Laser induction technology is used to cause an infrared laser to chemically react with the surface of polyimide and generate a continuous and uniform graphene layer on the surface of the polyimide. During the preparation process, the target product can be rapidly generated without the protection of an inert atmosphere, thereby realizing the preparation of graphene and the efficient combination of graphene materials and polyimide.
[0027] (2) The present invention chemically modifies or functionalizes the graphene surface to improve its hydrophobicity and make it hydrophilic, and uses a polyvinyl alcohol aqueous solution, polyacrylonitrile solution, chitosan and other strong hydrophilic substances to form a protective layer. The present invention has the characteristics of simple operation, economy, arbitrary patterning and wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0029] Figure 1 This is a schematic diagram of the graphene-polyimide-graphene composite film in Example 1 of the present invention.
[0030] Figure 2 This is a physical picture of the graphene-polyimide-graphene composite film in Example 1 of the present invention.
[0031] Figure 3 This is a Raman spectrum of the graphene layer in Example 1 of the present invention.
[0032] Figure 4 This is a scanning electron microscope image of the graphene layer in Example 1 of the present invention.
[0033] Figure 5 This is a schematic diagram of the surface contact angle of the graphene / polyimide / graphene three-dimensional structure permeable membrane modified with chitosan acetic acid aqueous solution in Example 1 of the present invention.
[0034] Figure 6 Schematic diagram of the surface contact angle of the graphene / polyimide / graphene three-dimensional structure permeable membrane modified with polyvinyl alcohol aqueous solution in Example 2 of the present invention.
[0035] Figure 7 Schematic diagram of the surface contact angle of the graphene / polyimide / graphene three-dimensional structure permeable membrane modified by polyacrylonitrile solution in Example 3 of the present invention.
[0036] Figure 8Schematic diagram of the surface contact angle of the polyimide film in Comparative Example 2 of the present invention.
[0037] Fig. 9 Schematic diagram of the surface contact angle of the graphene-polyimide-graphene composite film in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0041] The polyimide film used in the embodiments of the present invention was purchased from Dongguan Ronghui Insulation Materials Co., Ltd.
[0042] Example 1
[0043] This embodiment provides a method for preparing a graphene / polyimide / graphene three-dimensional structure permeable membrane.
[0044] Use polyimide film, which is about 100 microns thick, cut to 1 cm 2 The size of the polyimide film was laser-induced on both sides, the laser power was 5W, and the laser moving rate was 850mm / s to obtain a graphene-polyimide-graphene composite film.
[0045] 0.3 g of commercial chitosan powder (deacetylation degree ≥ 95%, viscosity 100-200 mPa.s) was dissolved in 20 mL of 1% acetic acid / water mixed solution, stirred for 2 h and ultrasonically treated to completely dissolve the chitosan to obtain a uniformly dispersed chitosan aqueous solution with a concentration of 1.5 wt%.
[0046] Take 15 μL of chitosan acetic acid aqueous solution and evenly apply the modifier on the front and back sides of the graphene-polyimide-graphene composite film by spraying, with a dosage of 15-20 μL / cm 2The spin coating parameters were 2500 rpm for 20 s and cured on a 70 °C hot plate for 1 hour to obtain a graphene / polyimide / graphene three-dimensional structure permeable membrane.
[0047] Graphene-polyimide-graphene composite film structure Figure 1 As shown, black represents the graphene layer and orange represents the PI layer.
[0048] Figure 2 This is a physical picture of the graphene-polyimide-graphene composite film.
[0049] Figure 3 This is the Raman spectrum of the graphene layer. It can be seen that the D peak of graphene is located at 1348.9668cm -1 The G peak is located at 1581.4043cm -1 The 2D peak is located at 2689.144 cm -1 The peak position of the test result corresponds to the standard Raman peak of graphene, proving that graphene material has been generated.
[0050] Figure 4 This is a scanning electron microscope image of the graphene surface. It can be seen that the graphene structure is arranged in a hole shape.
[0051] The contact angle test results of graphene / polyimide / graphene three-dimensional structure permeable membrane are as follows: Figure 5 shown.
[0052] Example 2
[0053] This embodiment provides a method for preparing a graphene / polyimide / graphene three-dimensional structure permeable membrane.
[0054] Use polyimide film, which is about 100 microns thick, cut to 1 cm 2 The size of the polyimide film was laser induced on both sides. During the preparation process, the laser power used was 5W and the laser moving rate was 850mm / s to obtain a graphene-polyimide-graphene composite film.
[0055] 1 g of commercial polyvinyl alcohol powder (Poly 1788 type) was dissolved in 19 g of water, heated in a water bath at 90° C., magnetically stirred for 1 h, and ultrasonically treated to completely dissolve the polyvinyl alcohol to obtain a uniformly dispersed polyvinyl alcohol aqueous solution with a mass concentration of 5 wt %.
[0056] Take 15 μL of the prepared polyvinyl alcohol aqueous solution and evenly apply the modifier on the front and back sides of the graphene-polyimide-graphene composite film by spin coating. The amount used is 15 μL / cm 2The spin coating parameters were 2500 rpm for 20 s and cured on a 70 °C hot plate for 1 hour to obtain a graphene / polyimide / graphene three-dimensional structure permeable membrane.
[0057] The generated graphene was tested by Raman spectroscopy, and the D peak of graphene was located at 1348.9668 cm -1 The G peak is located at 1581.4043cm -1 The 2D peak is located at 2689.7658 cm -1 The peak position corresponds to the standard Raman peak of graphene, proving that graphene material has indeed been generated.
[0058] The contact angle test results of graphene / polyimide / graphene three-dimensional structure permeable membrane are as follows: Figure 6 shown.
[0059] Example 3
[0060] This embodiment provides a method for preparing a graphene / polyimide / graphene three-dimensional structure permeable membrane.
[0061] Use polyimide film, which is about 100 microns thick, cut to 1 cm 2 The size of the polyimide film was laser-induced on both sides, the laser power was 10W, and the laser moving rate was 800mm / s to obtain a graphene-polyimide-graphene composite film.
[0062] 2 g of commercial polyacrylonitrile powder was dissolved in 18 mL of commercial 1-methyl-2-pyrrolidone (NMP), heated in a water bath at 90 degrees Celsius with stirring for 1 hour and ultrasonically treated to completely dissolve the polyacrylonitrile to obtain a uniformly dispersed polyacrylonitrile solution with a concentration of 10 wt%.
[0063] Take 15 μL of the prepared polyacrylonitrile solution and evenly apply the modifier on the front and back sides of the graphene-polyimide-graphene composite film by spin coating. The amount used is 15-20 μL / cm 2 The spin coating parameters were 2500 rpm for 20 s and cured on a 70 °C hot plate for 1 hour to obtain a graphene / polyimide / graphene three-dimensional structure permeable membrane.
[0064] The generated graphene was tested by Raman spectroscopy, and the D peak of the measured graphene was located at 1350.6369 cm -1 The G peak is located at 1586.2754cm -1 The 2D peak is located at 2691.1563 cm -1 At , the test results correspond to the standard peak, proving that graphene material has been generated.
[0065] The contact angle test results of graphene / polyimide / graphene three-dimensional structure permeable membrane are as follows: Figure 7 shown.
[0066] Comparative Example 1
[0067] The difference between this comparative example and Example 1 is that the modifier solution is directly coated on the surface of the original polyimide film, and the other steps are the same as those in Example 1, and the modifier coating fails.
[0068] Comparative Example 2
[0069] This comparative example directly uses the original polyimide film in Example 1.
[0070] Figure 8 Schematic diagram of the surface contact angle of polyimide film.
[0071] Comparative Example 3
[0072] This comparative example directly uses the graphene-polyimide-graphene composite film in Example 1.
[0073] Fig. 9 Schematic diagram of the surface contact angle of graphene-polyimide-graphene composite film.
[0074] By comparison Figure 5-9 It can be seen that the surface contact angle of the graphene / polyimide / graphene three-dimensional structure permeable membrane in Examples 1-3 is significantly smaller than that in Comparative Examples 2 and 3, and the hydrophilicity is effectively improved. Among them, the contact angle of the graphene / polyimide / graphene three-dimensional structure permeable membrane in Example 1 is the smallest, and the modification effect of the chitosan acetic acid aqueous solution is the best.
[0075] In summary, the present invention provides a method for preparing a graphene / polyimide / graphene three-dimensional structure permeable membrane, which utilizes laser induction technology to cause an infrared laser to chemically react with the surface of polyimide and generate a continuous and uniform graphene layer on the surface of the polyimide. During the preparation process, the target product can be rapidly generated without the protection of an inert atmosphere, thereby realizing the preparation of graphene and the efficient combination of graphene materials and polyimide. The present invention chemically modifies or functionalizes the surface of the graphene to improve its hydrophobicity and make it hydrophilic, and uses a polyvinyl alcohol aqueous solution, a polyacrylonitrile solution, a chitosan and other strongly hydrophilic substances to coat the membrane to form a protective layer. The method has the characteristics of simple operation, economy, arbitrary patterning and a wide range of uses.
[0076] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a graphene / polyimide / graphene three-dimensional structure permeable membrane, characterized in that: include, Laser-induced treatment of both sides of the polyimide film to obtain a graphene-polyimide-graphene composite film; The modifier is dissolved in a solvent, heated in a water bath, and stirred to obtain a uniformly dispersed modifier solution; The modifier solution is spin-coated on the front and back sides of the graphene-polyimide-graphene composite membrane and solidified to obtain a graphene / polyimide / graphene three-dimensional structure permeable membrane.
2. The method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane according to claim 1, characterized in that: The laser power of the laser induction is 5-10W, and the laser moving speed is 800-1000mm / s.
3. The method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane according to claim 1, characterized in that: The modifier includes one of polyvinyl alcohol, polyacrylonitrile and chitosan.
4. The method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane according to claim 3, characterized in that: The concentration of the modifier in the solvent is 1.5-10 wt %.
5. The method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane according to claim 4, characterized in that: The solvent includes one of water, 1-methyl-2-pyrrolidone or an aqueous solution containing acetic acid.
6. The method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane according to claim 5, characterized in that: The acetic acid concentration in the aqueous solution containing acetic acid is 1-2%.
7. The method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane according to claim 1, characterized in that: The water bath heating temperature is 90-95° C., and the heating time is 1-2 hours.
8. The method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane according to claim 1, characterized in that: The rotation speed of the spin coating is 2500-3000 rpm, and the time is 20-30s.
9. The method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane according to claim 1, characterized in that: The curing temperature is 70-75° C. and the curing time is 1-2 hours.
10. The method for preparing the graphene / polyimide / graphene three-dimensional structure permeable membrane according to claim 1, characterized in that: The dosage of the modifier solution is 15-20 μL / cm 2 .
Citation Information
Patent Citations
Methods for making laser-induced graphene and compositions thereof
CN110167877B